TEACHING ENGLISH USING CONTENT-BASED INSTRUCTION (CBI) IN IMPROVING STUDENTS’ ENGLISH SPEAKING SKILL (A Classroom Action Research in the Second Grade Students of PoltekparLombok) - Lalu Mahsar (Sekolah Tinggi Pariwisata Mataram, 2021)
This study examines the improvement of student speaking skill through content-based students’ English speaking skill. More specificly, this study : (1) finding to what extent content-based instruction improved the students’ speaking skill; and (2) to describe the teaching and learning situation when content-based instruction was applied in the speaking class. This study applied action research technique to conduct the research which is consisted of two cycles, with four meetings in each cycle; while each cycle consists planning, action, observation, and reflection. The research was conducted at Poltekpar Lombok Praya; the subjects of the research were the university students of second grade in the Academic year of 2018-2019. This study reveals that the teaching using CBI was effective in two aspects: (1) in improving students’ speaking ability: students’ speaking level increased; students could answer the teacher’s questions; students could fluently communicate with their friends by using correct grammatical forms and appropriate vocabulary with good pronunciation; the use of mother tongue was reduced; (2) in improving class situation: the atmosphere in the whole class became alive; students enjoyed the speaking activities; there were many chances for students to practice their speaking skill; students had great motivation to learn speaking; speaking became easy and fun to the students. This study futher showed that CBI was effective and beneficial to improve the students’ speaking competency and the classroom situation.